Improving Student’s Narrative Text Writing Skills Using Short Videos - Shofia Alya Dzakiriah; Dzul Rachman; Ibrahim (Journal of English Language Learning, 2025)
Writing narrative texts poses significant challenges for many EFL students, including difficulties in organizing ideas, using appropriate vocabulary, and applying correct grammar. This study explores the effectiveness of short videos in improving students’ narrative text writing skills, focusing on creativity, vocabulary, and writing structure. A quasi-experimental design with a one-group pre-test and post-test was used. The participants were 36 eighth-grade students from a junior high school. Data were collected using writing tests and questionnaires administered before and after the intervention. During the treatment, students were taught narrative writing through short video media, designed to provide visual and auditory input to stimulate ideas and model narrative structures. The results demonstrated a significant improvement in students' narrative writing performance, with average scores increasing from 51.53 in the pre-test to 80 in the post-test. Statistical analysis using the Wilcoxon Signed-Rank Test and Paired Samples t-Test confirmed the effectiveness of the intervention. Questionnaire findings also indicated increased motivation, engagement, and understanding of narrative elements. These outcomes suggest that integrating short videos into EFL writing instruction can enhance students’ creativity, enrich their vocabulary, and strengthen their ability to construct coherent narratives. The findings advocate for more dynamic and multimodal teaching approaches to support students in developing effective writing skills.